Control of mastitis in dairy sheep and goats. (2nd May 2021) - Manning, Al; Vasileiou, Natalia; Crilly, JP
Abstract : Clinical mastitis is much less common in dairy sheep and goats than in cattle, but it is still a major cause of loss and impaired welfare. Subclinical mastitis rates range from 5–30%, but it is a significant cause of lost production and impaired milk quality. Gram-positive bacteria, in particular Staphylococcus aureus and coagulase-negative staphylococci, and contagious modes of transmission predominate. Diagnosis is complicated by higher somatic cell counts (SCC) even in uninfected udders, particular in goats. Control of mastitis requires a multimodal approach involving treatment, culling, vaccination and steps to reduce transmission.